A comparative study of proximal femoral nailing and dynamic hip screw in the management of inter trochanteric fracture femur - V P Raman; P Vijaya Shankar (MRIMS Journal of Health Sciences, 2016)
Inter-trochanteric fractures of the femur are one of the most common fractures of the hip in the elderly. They occur usually due to low energy trauma like simple falls. The incidence is rising because of increased life expectancy. The prevalence of these fractures is related to numerous factors including osteoporosis, malnutrition, decreased physical activity, impaired vision, neurological impairment and altered muscle balance. The present study was a prospective randomized study consisting of 60 adult patients with fresh inter-trochanteric fractures of the femur who were treated with DHS or PFN at MediCiti institute of Medical Sciences Ghanpur, Rangareddy District, Andhra Pradesh between June 2010 and June 2012. This study was carried out to compare the results of inter-trochanteric fractures treated with DHS and PFN. All the 60 patients were followed up at regular intervals. Inter-trochanteric fractures were most common between the ages of 61-70 years in our series. A trivial fall at home was most common mechanism of injury (70%). Males outnumbered females. Type 1 and 2 (Boyd and Griffin) were most common. Blood loss was less for PFN (197 ml) as compared to DHS (304 ml). There were no significant differences in the intra-operative complications with both implants. The mean time for full weight bearing was 10.75 weeks for PFN and 14.42 weeks for DHS, for radiological union was 19.57 weeks for PFN and 22.04 Weeks for DHS. There were more excellent/good results with PFN (93%) as compared to DHS (78%). There was one poor result with DHS and none with PFN. Limb length discrepancy (>1cm) was equal in both groups (2 each).